Aurantio-Obtusin Stimulates Chemotactic Migration and Differentiation of MC3T3-E1 Osteoblast Cells - Vishnuprasad, Chethala N.; Tsuchiya, Tomoko; Kanegasaki, Shiro; Kim, Joon Ho; Han, Sung Soo (Planta Medica, 2014)
Osteoporosis is one of the major metabolic bone diseases and is among the most challenging noncommunicable diseases to treat. Although there is an increasing interest in identifying bioactive molecules for the prevention and management of osteoporosis, such studies principally focus only on differentiation and mineralization of osteoblasts or inhibition of osteoclast activity. Stimulation of osteoblast migration must be a promising osteoanabolic strategy for improved metabolic bone disease therapy. In this study, we show that an anthraquinone derivative, aurantio-obtusin, stimulated chemotactic migration of MC3T3-E1 osteoblast cells in a concentration-dependent manner. The use of a real-time chemotaxis analyzing system, TAXIScan, facilitated the evaluation of both velocity and directionality of osteoblast migration in response to the compound. Besides migration, the compound stimulated osteoblast differentiation and mineralization. Taken together, the data presented in this paper demonstrate that aurantio-obtusin is a promising osteoanabolic compound of natural origin with potential therapeutic applications in the prevention of osteoporosis and other metabolic bone diseases.
Keywords: aurantio-obtusin; TAXIScan; chemotaxis; osteoblast migration; differentiation; mineralization